2022
DOI: 10.1002/mds.29057
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and Subthalamic Nucleus Spectral Changes During Limb Movements in Parkinson's Disease Patients with and Without Dystonia

Abstract: Background Dystonia is an understudied motor feature of Parkinson's disease (PD). Although considerable efforts have focused on brain oscillations related to the cardinal symptoms of PD, whether dystonia is associated with specific electrophysiological features is unclear. Objective The objective of this study was to investigate subcortical and cortical field potentials at rest and during contralateral hand and foot movements in patients with PD with and without dystonia. Methods We examined the prevalence and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
1
5
1
Order By: Relevance
“…Despite the postoperative stun effect as a potential confounder in this study, our results are confirmed by a previous report that did not find increased theta power in the STN of dystonia patients, which could be due to differences in input between the GPi and STN 35 . Another recent study indicates that dystonia‐related spectral changes in the STN may be more prominent during voluntary movements; however, this study investigated dystonia as a motor sign of PD instead of isolated dystonia 36 …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Despite the postoperative stun effect as a potential confounder in this study, our results are confirmed by a previous report that did not find increased theta power in the STN of dystonia patients, which could be due to differences in input between the GPi and STN 35 . Another recent study indicates that dystonia‐related spectral changes in the STN may be more prominent during voluntary movements; however, this study investigated dystonia as a motor sign of PD instead of isolated dystonia 36 …”
Section: Discussionsupporting
confidence: 87%
“…35 Another recent study indicates that dystonia-related spectral changes in the STN may be more prominent during voluntary movements; however, this study investigated dystonia as a motor sign of PD instead of isolated dystonia. 36 Contrary to the prominent beta peaks in STN that are a hallmark of PD, 37,38 we did not observe a clear beta peak in the STN of dystonic patients (Fig. 1C), despite other studies showing beta activity in the STN of dystonic patients at rest 35 and subthalamic beta peaks in patients with obsessive compulsive disorder.…”
Section: Spectral Features Of the Dystonic Stn And Thalamuscontrasting
confidence: 87%
See 1 more Smart Citation
“…Given the mixed findings from various groups, correlations between local field potentials and motor efficacy should be studied prospectively in larger samples and with chronic recordings >4 weeks after implant. Importantly, even if beta cannot consistently inform selection of directional contacts, it is nevertheless an important component of field potential signals arising from central motor circuits 37,38 and still might prove useful as a control signal for adaptive stimulation. 39 Also, the asymmetric 1-3-3-1 design of first generation directional electrodes complicates interpretation because the surface area of the ring contacts (1 and 8) differs substantially from the smaller directional contact segments.…”
Section: Discussionmentioning
confidence: 99%
“…Motor symptom asymmetry is a defining clinical feature of PD. Our routine clinical practice is to treat the most severely affected hemibody with unilateral DBS, followed by staged surgery on the opposite side of the brain (when, and if, needed) [24][25][26][27][28] . The same neurosurgeons (BG, JNB) implanted a 1-3-3-1 directional lead (Boston Scientific Vercise DBS system, Natick MA, USA, FDA IDE# G170063) at the STN target under local anesthesia with the patient fully awake.…”
Section: Surgical Procedures and Stimulation Parametersmentioning
confidence: 99%